Association between duration of residence and prevalence of type 2 diabetes among male South Asian expatriate workers in the United Arab Emirates: a cross-sectional study. Issue 12 (17th December 2020) - Shah, Syed M; Jaacks, Lindsay M; Al-Maskari, Fatima; Al-Kaabi, Juma; Aziz, Faisal; Soteriades, Elpidoforos; Loney, Tom; Farooqi, Hamed; Memon, Anjum; Ali, Raghib
Abstract : Expatriates account for about 80% of the total population in the United Arab Emirates (UAE). This study aimed to evaluate the hypothesis that prevalence of type 2 diabetes in male South Asian expatriates increases with increased length of residence in the UAE. Design, settings and participants: This cross-sectional study recruited a representative sample (n=1375) of male South Asian expatriates aged ≥18 years in Al Ain, UAE. Sociodemographic, anthropometric and lifestyle data were obtained using a pilot-tested adapted version of the WHO STEPS instrument. Main outcome measures: Duration of residence was used as a marker for acculturation. Type 2 diabetes was defined as a self-reported physician diagnosis of diabetes or a glycosylated haemoglobin blood level ≥6.5%. Results: Mean (±SD) age of participants was 34.0±9.9 years. Overall, the prevalence of type 2 diabetes was 8.3% (95% CI 6.8% to 9.8%). Diabetes prevalence was positively associated with longer duration of residence in the UAE, 2.7%, <5 years; 8.2%, 5–10 years; and 18.8%, >10 years. After adjusting for age, nationality, and income and age, expatriates were more likely to develop diabetes if residing in the UAE for 5–10 years (OR=2.18; 95% CI 1.02 to 4.67) or >10 years (OR=3.23; 95% CI 1.52 to 6.85) compared with those residing for <5 years. Conclusions: After controlling for potential confounding factors, longer duration of residence was significantly associated with a higher prevalence of type 2 diabetes in male South Asian expatriate workers in the UAE.